Analisis Kemampuan Membaca Kritis Mahasiswa Pendidikan Bahasa Dan Sastra Indonesia Dalam Memahami Teks Akademik Berdasarkan Taksonomi Barrett - Mohammad Fikriandi Ramdhansyah; Asep Nurjamin (Advances In Education Journal, 2026)
This study aims to describe the critical reading ability of third-year students in the Indonesian Language and Literature Education Program at the Indonesian Institute of Education in understanding academic texts based on Barrett’s Taxonomy. The research employed a quantitative descriptive design with a survey approach. The participants consisted of 26 students selected through total sampling. Data were collected using a reading comprehension test in the form of essay questions developed according to the five levels of Barrett’s Taxonomy: literal, reorganization, inferential, evaluative, and appreciative. Data analysis was conducted descriptively by calculating scores, percentages, and categorizing students’ levels of critical reading ability. The results indicate that students’ critical reading ability falls into the good category, with an average percentage of 71.60%. The literal indicator obtained the highest score at 83.75%, followed by reorganization (77.00%) and inferential (71.25%). The evaluative and appreciative indicators showed lower scores of 65.50% and 60.50%, respectively. The distribution of scores reveals that 38.46% of students were in the good category and 23.08% in the very good category, while 11.54% remained in the low category. These findings suggest that students are able to understand explicit information, draw conclusions, and evaluate texts logically; however, their reflective and appreciative abilities still need improvement. The application of Barrett’s Taxonomy proved effective in systematically mapping students’ critical reading levelsof abilities. The findings are expected to serve as a basis for developing more structured, contextual, and higher-order-thinking-oriented critical reading instruction in higher education. Kata kunci: critical reading, academic texts, Barrett’s Taxonomy, quantitative descriptive